2014
DOI: 10.1002/asia.201402580
|View full text |Cite
|
Sign up to set email alerts
|

[Fe(F20TPP)Cl]‐Catalyzed Amination with Arylamines and {[Fe(F20TPP)(NAr)](PhINAr)} Intermediate Assessed by High‐Resolution ESI‐MS and DFT Calculations

Abstract: Amination of CH bonds catalyzed by transition metal complexes via nitrene/imide insertion is an appealing strategy for CN bond formation, and the use of iminoiodinanes, or their in situ generated forms from 'PhI(OAc)2 +primary amides (such as sulfonamides, sulfamates, and carbamates)', as nitrogen sources for the amination reaction has been well documented. In this work, a 'metal catalyst+PhI(OAc)2 +primary arylamines' amination protocol has been developed using [Fe(F20 TPP)Cl] (H2 F20 TPP=meso-tetrakis(pent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 61 publications
0
19
0
1
Order By: Relevance
“…Another cationic complex, which includes an iron(IV) ion has been intercepted as ap utative intermediate of the nitrene/imide insertion and transfer reaction using arylamines. [54] In ar ecent contribution from our group,w ei nvestigated the copper-catalyzed azide alkyne cycloaddition (CuAAC) by offline ESI-MS(/MS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another cationic complex, which includes an iron(IV) ion has been intercepted as ap utative intermediate of the nitrene/imide insertion and transfer reaction using arylamines. [54] In ar ecent contribution from our group,w ei nvestigated the copper-catalyzed azide alkyne cycloaddition (CuAAC) by offline ESI-MS(/MS).…”
Section: Methodsmentioning
confidence: 99%
“…Another cationic complex, which includes an iron(IV) ion has been intercepted as ap utative intermediate of the nitrene/imide insertion and transfer reaction using arylamines. [54] In ar ecent contribution from our group,w ei nvestigated the copper-catalyzed azide alkyne cycloaddition (CuAAC) by offline ESI-MS(/MS). [2e] Its challenging mechanism had been previously addressed by several theoretical and experimental studies,w hich suggested am echanism involving binuclear copper intermediates.W et hen analyzed two different CuAACr eaction mixtures,o ne containing classic neutral reactants and the second containing imidazolium-based charged alkyne.T he approach, in both cases,a llowed, for the first time,i nterception and full characterization of the crucial bis(copper) intermediates like bis(copper) acetylides and triazoles (Figure 12).…”
Section: Methodsmentioning
confidence: 99%
“…Insbesondere der Eisen(IV)‐Komplex, der die Fe=O‐Einheit enthält, wurde als katalytisch effektiv identifiziert. Ein weiterer kationischer Komplex mit dem Eisen(IV)‐Ion wurde als mögliche Zwischenstufe bei der Nitren/Imid‐Insertion und der weiteren Übertragung mit Arylamiden abgefangen …”
Section: Homogene Metallkatalyseunclassified
“…The development of efficient synthetic procedures to attain aminated compounds is of paramount importance due to pharmaceutical and/or biologic behaviours of aza-containing molecules. [1] Amongst all the catalysts capable of promoting amination reactions, ruthenium(II) porphyrin complexes [2][3][4] show a good efficiency in catalysing the amination of saturated and unsaturated hydrocarbons by using different classes of aminating agents such as aryl iminoiodinanes (RN=IAr) [5], amines in the presence of oxidant species [6] and organic azides (RN 3 ) [7][8][9][10][11]. Numerous structural modifications of the porphyrin skeleton were carried out to improve the catalytic performance which can also be modulated by the electronic nature of the axial ligands onto the ruthenium(II) centre [12,13].…”
Section: Introductionmentioning
confidence: 99%